Aplikasi Metode VIKOR untuk Menentukan Penerimaan Proposal Kegiatan Desa - SUKAMTO TO; Yanti Andriyani; Ibnu Daqiqil Id (Politeknik Caltex Riau, 2022)
The office of the Wali Nagari Simpang has a proposal for village activities. The evaluating proposals is carried out directly in the field and is done manually, so it is possible for errors to occur. For that we need a decision support system using the VIKOR method. The final result of the five proposals submitted with the specified criteria, provides a recommendation that the proposal Jembatan Kp. Batuang - Bukik Putuih is the best proposal and deserves to be funded